N.F. Fedorov philosophy of nature regulation and modernity - I. V. Brylina (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The urgency of the discussed issue is caused by the need to remember the Russian philosopher, humanist, cosmist N. F. Fedorov who offered mankind a transition to energy-efficient and resource-saving technologies more than a century ago. He insisted on using the army for peaceful purposes. He also predicted the emergence of «global environmental problems» which humanity faced in the twentieth century. The main aim of the study is to analyze the works of N. F. Fedorov and their influence on the development of philosophical and scientific thought of today, to describe his original project of the nature regulation, which became a source of evolutionary concept of the noosphere, transhumanism and many other branches of modern scientific knowledge. Conclusion: The author states that the main law of nature (Death) is the common enemy of mankind (Evil). The paper describes a mechanism of nature regulation and its driving force. It is love to fathers (the resurrection of the ancestors), which is the basis of the immortology as the science of overcoming Death in the twentieth century.